Răspuns :
[tex]D(a) = \left[\begin{array}{ccc}a&-1&1\\-1&1&a\\-1&a&1\end{array}\right] = [/tex]
[tex]=(a+a-a)+(1-1-a^{3} ) = a-a^{3} = a(1-a^{2}) = [tex]a(1-a)(1+a) \leq 0[/tex][/tex]
= (a + a - a) + (1 - 1 - a³ )
[tex]D(a) \leq 0[/tex]
[tex]a(1 - a)(1 + a) \leq 0[/tex]
Va trebui sa rezolvam ecuatia:
a(1 - a)(1 + a) = 0
a₁ = 0
a₂ = 1
a₃ = -1
Vom da valori cuprinse intre radacini si in afara lor pentru a vedea semnul functiei.
a = -2 < -1 => -2 * (1 + 2)(1 - 2) = +6 => D(a) > 0 pe (-∞, -1)
a = -0,5 intre -1 si 0 => -0,5 * (1 + 0,5)(1 - 0,5) = -0,375 => D(a) ≤ 0 pe [-1, 0]
a = 0,5 intre 0 si 1 => 0,5 * (1 - 0,5)(1 + 0,5) = +0,375 => D(a) > (0, 1)
a = 2 > 1 => 2 * (1 - 2)(1 + 2) = -6 => D(a) ≤ 0 pe [1, ∞)
D(a) ≤ 0 daca
a ∈ [-1, 0] U [1, ∞)
[tex]=(a+a-a)+(1-1-a^{3} ) = a-a^{3} = a(1-a^{2}) = [tex]a(1-a)(1+a) \leq 0[/tex][/tex]
= (a + a - a) + (1 - 1 - a³ )
[tex]D(a) \leq 0[/tex]
[tex]a(1 - a)(1 + a) \leq 0[/tex]
Va trebui sa rezolvam ecuatia:
a(1 - a)(1 + a) = 0
a₁ = 0
a₂ = 1
a₃ = -1
Vom da valori cuprinse intre radacini si in afara lor pentru a vedea semnul functiei.
a = -2 < -1 => -2 * (1 + 2)(1 - 2) = +6 => D(a) > 0 pe (-∞, -1)
a = -0,5 intre -1 si 0 => -0,5 * (1 + 0,5)(1 - 0,5) = -0,375 => D(a) ≤ 0 pe [-1, 0]
a = 0,5 intre 0 si 1 => 0,5 * (1 - 0,5)(1 + 0,5) = +0,375 => D(a) > (0, 1)
a = 2 > 1 => 2 * (1 - 2)(1 + 2) = -6 => D(a) ≤ 0 pe [1, ∞)
D(a) ≤ 0 daca
a ∈ [-1, 0] U [1, ∞)